PENERAPAN MODAL SOSIAL SIMPAN PINJAM PEREMPUAN (SPP) NENAS DI JORONG KOTO TUO NAGARI LUBUK TAROK KECAMATAN LUBUK TAROK KABUPATEN SIJUNJUNG - Agnes Adelina; Ikhsan Muharma Putera; Wibi Wijaya (Department of History Education, Faculty of Social Science, Universitas Negeri Medan, 2023)
The presence of groups in the implementation of Savings and Loans for Women (SPP), shows that the activities of this SPP group have stimulated the formation of groups in the community. This creates a cooperation in the social relations they live. So this is what gives rise to a capital known as social capital. The purpose of this study was to determine the Application of Social Capital for Women's Savings and Loans Group (SPP) Pineapple in Jorong Koto Tuo Nagari Lubuk Tarok, Lubuk Tarok District, Sijunjung Regency. The theory used in this study is the Social Capital theory proposed by Robert Putman. The research was conducted in Jorong Koto Tuo Nagari, Lubuk Tarok, Lubuk Tarok District, Sijunjung Regency. This study uses qualitative research methods with descriptive research type. The withdrawal of informants was carried out by purposive sampling technique. The data collection method in this study began with observation, in-depth interviews, and document studies. Data analysis was carried out in several stages, namely, data collection, data reduction, data presentation and drawing conclusions. The results showed that the existing social capital in the Women's Savings and Loans Group (SPP) refers to networks, norms and trust as well as cooperation that has the potential to increase the productivity of its members. Women's savings and loan groups (SPP) need networks, norms, and trust and cooperation as social capital.